Effectiveness of application technology-based basic life support training method on cardiopulmonary resuscitation accuracy: A Systematic Review - Mega Utami; Sidik Awaludin (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Professionals' knowledge and abilities can be enhanced by the effective and efficient use of technology in BHD training. In order to better study and assess the impact of application-technology based basic life support training techniques on the precision of cardiopulmonary resuscitation procedures, we plan to assess the existing research, which was published between 2014 and 2024. Purpose: To examine application-technology-based basic life support training approaches affected the precision of cardiac resuscitation techniques. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Individuals who received Basic Life Support (BLS) training, I: Technology application-based BLS training method, C: Conventional BLS training method or no app-based training, O: Accuracy in performing cardiopulmonary resuscitation (CPR), and S: Randomized controlled trial. The article search was conducted systematically using the keywords: Basic Support" AND "Cardiopulmonary Resuscitation" AND "CPR training with application guideline" AND "Conventional CPR training" AND "Accuracy of CPR performance. Results: Basic Life Support (BLS) instruction shows varying effects on knowledge and skills in administering Cardiopulmonary Resuscitation (CPR). Training using applications presents both advantages and disadvantages. One notable advantage is the use of digital platforms to deliver learning materials in a more interactive and dynamic way, thereby increasing trainees’ accessibility to relevant and up-to-date information. Conclusion: That technology-based Basic Life Support (BLS) training applications are effective in improving the accuracy of Cardiopulmonary Resuscitation (CPR). Applications featuring real-time feedback, Virtual Reality (VR) simulations, and interactive smartphone guides significantly improve the standard of CPR techniques and chest compressions in comparison to traditional approaches.